Hepatic - jejunoduodenostomy palliative lateral-lateral unresectable pancreatic cancer at risk of duodenal occlusion - Praderi, Raúl; Juambeltz, Nelson; Colet, Andrés; Mori, Raúl; Lago, Fernando; Hernández, Alejandro (Cirugía del Uruguay, 1992)
In arder to achieve good pallation of pancreatic cancer, it is convenient to make a high hepatico---1ejunal anastomosis, after sectioning and abandoning the lower end of the choledochus over the tumor.